Calcium, magnesium and potassium in mineral soils from the southern half of Finland - Kaila, Armi (Agricultural and Food Science, 1973)
210 samples of mineral soils from the southern half of Finland with mainly an acid precambrian bedrock, were analysed for the total contents of Ca, Mg and K, and for the portion of these nutrients which could be exchanged by N NH4OAc (pH 7), dissolved by 0.1 N HCI at room temperature, or released by N HCI at 50° C. The total content of Ca was lowest in samples of heavy clay, 0.78±0.14 % in the surface soils and 0.92±0.10 % in the deeper layers. The mean content in the groups of other soils was at least about 1.1 %. The total content of Mg increased with an increase in the clay content (r = 0.81***). It ranged from 0.6±0.1 % in the sand and fine sand samples to 1.53±0.19 % in the heavy clay soils of the surface layers and to 1.89±0.12 % in those of the deeper layers. Also in the groups of loam and silt soils and of the coarser clay soils, respectively, the Mg content was in the deeper layers higher than in the surface soils. The total content of K also increased with the clay content (r=0.73***) from 1.7±0.1 % in the sand and fine sand soils to 2.74±0.21 % in the heavy clay soils of the surface layers and to 3.10±0.07 % in those of the deeper layers. The portion of exchangeable Ca was relatively high: in the groups of surface soils from more than one tenth to one third of the total amount. The corresponding average amounts released by even the more drastic treatment with acid were not markedly higher. Only a few per cents of total Mg were exchangeable and slightly higher amounts were dissolved by 0.1 N HCI, whereas the treatment with N HCI at 50° C released about half of the total Mg. Exchangeable K and K dissolved by 0,1 N HCI did not exceed 1 % of the total K, except slightly in the heavy clay soils; the average amounts released by N HCI ranged from 5 to 18 % of the total K. The plant availability of these nutrients was discussed.